Combination of salicylic acid, malic acid and urea enhances the vase life of cut gerbera flowers on par with selected treatments. (13th April 2015) - Jamshidi, Maryam; Hadavi, Ebrahim; Naderi, Roohangiz
We evaluated the effect of three levels of salicylic acid (0, 1 and 2 mM), malic acid (0, 2 and 4 mM) and urea (0, 0.5 and 1.5 mM) in vase solution on postharvest performance parameters of cut flowers. The treatments were compared with two external control treatments (including 12 hours pulsing with SNP 5 mg 1 −1 + Suc 6% w/v and continuous treatment with 20 g 1 −1 Suc + 200 mg l −1 8–HQC + 150 mg 1 −1 citric acid + 1g 1 −1 CaCl2 ). Data were analysed with SPSS software, and mean comparison was performed using Duncan's test. The longest flower vase–life was recorded in treatment with (salicylic acid 1 mM + malic acid 2 mM + urea 0.5 mM) with average vase life of 17 days compared to 16.4 and 16.3 days in external controls and 9.3 days in internal control (distilled water). The results suggest that combinations of malic acid, salicylic acid and urea could be considered feasible low–price alternatives for currently used agents in gerbera vase solutions.